2018
DOI: 10.1007/s12289-017-1395-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internal pressure on springback during low pressure tube hydroforming

Abstract: For the existence of bending deformation during low pressure tube hydroforming(LPTH), springback is unavoidable and deteriorate the forming accuracy. In this paper, an analytical model of springback for LPTH was proposed. The simulation and experiment were carried out to investigate the effects of the main factors on the springback, such as internal pressure, corner radius and thickness. The results indicate that, different from expansion deformation, bending forming is the main and basic deformation for tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…They analytically obtained springback in bulge forming and validated the analytical model using both experimental tests and numerical simulations. Chu et al [14] proposed an analytical model for springback in low-pressure tube hydroforming (LPTH) based on classical elasticity theory. The classical theory of elasticity assumes a direct correlation between springback and the bending moment in the forming of tubes.…”
Section: Introductionmentioning
confidence: 99%
“…They analytically obtained springback in bulge forming and validated the analytical model using both experimental tests and numerical simulations. Chu et al [14] proposed an analytical model for springback in low-pressure tube hydroforming (LPTH) based on classical elasticity theory. The classical theory of elasticity assumes a direct correlation between springback and the bending moment in the forming of tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Chu et alstudied the springback of rectangular component in LPTH process. And proposed a forming process, tube hydro-forging(THFG), for forming variable cross-section at low hydraulic pressure[8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that the required internal pressure and die closing force for low pressure tube hydroforming is much less than that of high pressure tube hydroforming. Chu et al [5] predicted the effect of internal pressure on the springback during low pressure tube hydroforming. However, the hydroforming process leads to rupture or folding defects for low-ductility materials such as high strength steel tubes.…”
Section: Introductionmentioning
confidence: 99%